Toward the total synthesis of grayanane diterpene mollanol A by a Prins [3 + 2] strategy. Issue 10 (26th February 2020) - Miao, Jianzhuang; Zheng, Yi-Xuan; Wang, Linna; Lu, Shi-Chao; Zhang, Shi-Peng; Gong, Ya-Ling; Xu, Shu
Abstract : A Prins-type [3 + 2] cyclization to form a five-membered ring was developed using an unprotected hydroxyaldehyde and activating-group-free olefins, which efficiently constructed the ADE ring segment of mollanol A. Abstract : Toward the total synthesis of a novel grayanoid, mollanol A, we developed a concise convergent strategy based on a formal [3 + 2] cyclization initiated by the Prins reaction. In this key intermolecular reaction between an unprotected hydroxyaldehyde and activating-group-free olefins, two chiral carbons and one densely substituted tetrahydrofuran ring were constructed stereoselectively.